Electoral Institutions, Cleavage Structures, and the Number of Parties - Neto, Octavio Amorim; Cox, Gary W. (American journal of political science, 1997)
A classic question in political science concerns what determines the number of parties that compete in a given polity. Broadly speaking, there are two approaches to answering this question, one that emphasizes the role of electoral laws in structuring coalitional incentives, and another that emphasizes the importance of preexisting social cleavages. In this paper, we view the number of parties as a product of the interaction between these two forces, following Powell (1982) and Ordeshook and Shvetsova (1994). The effective number of parties in a polity should be a multiplicative rather than an additive function of the permissiveness of the electoral system and the heterogeneity of the society. Multiple regression on cross-sectional aggregate electoral statistics. Unlike previous studies, we (1) do not confine attention to developed democracies; (2) explicitly control for the influence of presidential elections, taking account of whether they are concurrent or nonconcurrent, and of the effective number of presidential candidates; and (3) also control for the presence and operation of upper tiers in legislative elections. The hypothesis is confirmed, both as regards the number of legislative parties and the number of presidential parties.